Dampak Tanggungjawab dan Pelatihan Auditor Internal terhadap Pendeteksian Kecurangan yang Dimoderasi Audit Jarak Jauh - Prameswari, Sielly Budi (Owner : Riset dan Jurnal Akuntansi, 2024)
The entities suffer material and non-material losses from fraudulent acts by employees. Indonesia is one of the countries with the highest corporate fraud rates in Asia Pacific. To minimize the occurrence of fraud, the role of internal auditors is needed. To detect fraud, internal auditors shall receive continual training. As is known, since the pandemic broke out, internal auditors have also conducted audits remotely. This study aims to examine the effect of internal auditors’ responsibility and training on fraud detection moderated by remote auditing in Indonesia. This study uses primary data. The population of this research is internal auditors from various types of institutions in Indonesia. Judgment sampling method is used. The sample consisted of 43 respondents. The research hypotheses were tested using multiple regression analysis. The results of the study prove that the responsibility and training of internal auditors have positive and significant effects on fraud detection. However, remote auditing is not proven to moderate the effects of internal auditors' responsibility and training on fraud detection. This study enriching the literature regarding the determination factors of responsibility and training of internal auditors on fraud detection. In addition, this research also proves that remote auditing in Indonesia is still relatively difficult to do, so that it can be used as an evaluation material for various entities to improve in the near future